A scoping review of evidence for the effects of seven global deer species on woody vegetation - Amy Gresham; John R. Healey; Peter J. Lawrence; Markus P. Eichhorn; Graeme Shannon (Ecological Solutions and Evidence)
Abstract Context: Rapid expansion of deer (Cervidae) populations is a concern for forest ecosystems. Despite extensive reviews on how deer affect forests, variation in effects across deer species has received less attention. A lack of focus on species‐specific effects may lead to oversights and failure to achieve desired management outcomes. Methodology: We used a systematic approach to compile data on the extent to which the effects of seven deer species on woody vegetation have been studied. We focused on the six deer species present in Britain and Ireland, and elk (Cervus canadensis). Results: A total of 455 studies were included from across the globe. Red deer (Cervus elaphus) (n = 163) and elk (n = 158) were the most studied species, while Reeve's muntjac (Muntiacus reevesi) (n = 18) and Chinese water deer (Hydropotes inermis) (n = 5) were the least researched. Fifty‐four per cent of studies (n = 245) used fenced exclosures to assess deer impacts. Research mainly focused on defoliation via browsing and grazing (n = 424), while debarking (n = 44), defecation (n = 8) and trampling (n = 5) were less frequently studied. Vegetation density (n = 235), height (n = 189) and diversity (n = 135) were the most common metrics used, while fewer studies focused on vegetation mortality (n = 74), structural variability (n = 28) and condition (n = 15). Practical implication: While previous studies have often focused on the probability or severity of deer damage to woody vegetation, we identified key knowledge gaps on the ecological influence of such damage, with a species‐specific focus. Researchers should treat deer species as distinct entities and appreciate the differences in their body size, sociality, physiology and behaviour when studying their ecological effects. Where multiple deer species co‐occur, identifying relative local species abundance and differences among species foraging behaviours will help to determine how their interactions—whether additive, synergistic or antagonistic—affect ecosystem processes and vegetation dynamics.